"Let me be Direct": Using Direct Assessments with Student leaders. Issue 6 (January 2013) - Lindsay, Nathan; Hourigan, Aimee; Smist, Jennifer; Wray, Larry
Nathan Lindsay, Aimee Hourigan, Jennifer Smist, and Larry Wray discuss the benefits of direct assessment of student learning in a variety of co-curricular programs.